The forgotten tonsils—does the immune active organ absorb nanoplastics? - Ekvall, Mikael T.; Naidu, Shanti; Lundqvist, Martin; Cedervall, Tommy; Värendh, Maria (Frontiers in Nanotechnology, 2022)
Nanoplastics are defined as plastic particles broken down to extremely small sizes (1-100 nm) with unknown effects to the human body and immune system. Air and food exposure scenarios involving blood, lungs and intestine are considered in the literature. The fact that plastics also needs to pass the nose, oral cavity, and throat is so far ignored in the literature. The tonsils are immunologically important tissue in the oral cavity in which ingested and inhaled agents are incorporated through crypts with the capacity to capture agents and start early immunologic reactions. We argue that the tonsil is a very important tissue to study in regard to micro and nanoplastic human exposure and immunologic response. Nano-sized particles are known to be able to travel through the natural barriers and have different effects on biology compared to larger particle and the bulk material. It is therefore, although difficult, important to develop experimental methods to detect and identify nanoplastics in the tonsils. In preliminary experiments we have optimized the breakdown of tonsil tissues and tried to retrieve added polystyrene nanoparticles using density-based separation and concentration. The polystyrene was followed by FTIR spectrometry and could be detected in micro- and nano-size, in the tissue breakdown solution but not after density-based separation. When nanoplastics are incorporated in the human body, it is possible that the small plastic pieces can be detected in the tonsil tissue, in the lymph system and it is of importance for future studies to reveal the immunological effects for humans.